2015
DOI: 10.1177/2158244015585606
|View full text |Cite
|
Sign up to set email alerts
|

The Relationships Between Need for Cognition, Boredom Proneness, Task Engagement, and Test Performance

Abstract: Participants read a procedural text describing how to make a wind-up spool toy while only reading, reading and watching the experimenter do the task, or reading and doing the task themselves. Afterward, task performance (measured by time to complete the task without the instructions and number of errors) and memory for/understanding of the text (measured with a Multiple Choice Test) were assessed. Participants then completed a packet that included the Need for Cognition and Boredom Proneness scales. Task perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…The narrative texts did not fit the goal of performing the actions as well as the list-like texts did, so the participants may have had to work harder in processing the narrative text to fit with that goal. A similar finding occurred the Diehl and Wyrick (2015) study, where a narrative procedural text was used and performance on a true-false test (a measure of the textbase) was moderated by “need for cognition” in the participants. Need for cognition was defined as “a measure of cognitive motivation that accesses the extent to which a person looks for and likes engaging in mentally stimulating activities” (p. 1).…”
Section: Discussionsupporting
confidence: 65%
“…The narrative texts did not fit the goal of performing the actions as well as the list-like texts did, so the participants may have had to work harder in processing the narrative text to fit with that goal. A similar finding occurred the Diehl and Wyrick (2015) study, where a narrative procedural text was used and performance on a true-false test (a measure of the textbase) was moderated by “need for cognition” in the participants. Need for cognition was defined as “a measure of cognitive motivation that accesses the extent to which a person looks for and likes engaging in mentally stimulating activities” (p. 1).…”
Section: Discussionsupporting
confidence: 65%
“…Research has shown a positive relationship between inattention, as measured by the ARCES, CFQ, and MAAS (Cheyne et al, 2006), and boredom proneness, as measured using the Boredom Proneness Scale. Further, Diehl and Wyrick (2015) found that individuals with a low need for cognition were more prone to boredom. Additionally, these same individuals performed worse on learning engagement and complex tasks, suggesting that they also experienced more lapses in attention (Diehl & Wyrick, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Further, Diehl and Wyrick (2015) found that individuals with a low need for cognition were more prone to boredom. Additionally, these same individuals performed worse on learning engagement and complex tasks, suggesting that they also experienced more lapses in attention (Diehl & Wyrick, 2015). It is possible that scores on the ARCES, CFQ, and MAAS also differ depending on level of education, but to our knowledge, this relationship has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between task involvement and need for cognition has been previously discussed in literature (Diehl and Wyrick, 2015; Cacioppo and Petty, 1982), which established that together they lead to high levels of cognitive processing that induce beliefs which impact on the attitude formation (Priluck and Till, 2004). In the decision-making context, individuals in high need for cognition put greater emphasis on attribute processing, and the use of elaborate methods to seek and process information (Mantel and Kardes, 1999; Fortier and Burkell, 2014).…”
Section: Extensions To the Conceptual Modelmentioning
confidence: 99%